Changes In The Level Of Knowledge And Attitudes Of Adolescent Girls After Providing Health Education About Fluor Albus At Gunungjati Twin Middle School - Nanda Rida Wihasti (International Journal of Health Engineering and Technology, 2026)
Vaginal discharge (fluor albus) is a reproductive health problem frequently experienced by adolescent girls and is often considered a normal condition, thus receiving little attention. Lack of appropriate knowledge and attitudes can influence reproductive hygiene behavior and increase the risk of pathological fluor albus. This study aims to determine changes in the level of knowledge and attitudes of adolescent girls after health education about fluor albus was provided at Gunungjati Kembaran Junior High School. The study used a quantitative approach with a pre-test design.‑One Group Pretest–Posttest experimental study. The population was all female adolescents at Gunungjati Kembaran Junior High School with a total sample of 29 respondents. Data collection was conducted using a knowledge and attitude questionnaire, then analyzed descriptively using univariate analysis, paired sample t-test, and Wilcoxon Signed Rank Test. The results showed an increase in the average knowledge score from 56.62 before the intervention to 74.62 after the intervention (p = 0.000). All respondents had a positive attitude after the intervention with no remaining negative attitudes. In conclusion, health education about fluor albus had a significant effect in improving the knowledge and attitudes of female adolescents in maintaining reproductive organ hygiene, thus proving this intervention effective.